2016
DOI: 10.1016/j.devcel.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

A Case for Distributed Control of Local Stem Cell Behavior in Plants

Abstract: Summary The root meristem has a centrally located group of quiescent cells, to which current models assign a stem cell organizer function. However, evidence is emerging for decentralized control of stem cell activity, where self-renewing behavior emerges from the lack of cell displacement at the border of opposing differentiation gradients. We term this a “stagnation” model due to its reliance on passive mechanics. The position of stem cells is established by two opposing axes that reciprocally control each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…Cell fate determination in plants mainly relies on positional information provided by perception of hormone gradients and non-cell autonomous factors (50-52). The expanded family of plant RLK proteins and their ligands play central roles in intercellular communication, cell identity maintenance, and the regulation of cell expansion and proliferation (53).…”
Section: Discussionmentioning
confidence: 99%
“…Cell fate determination in plants mainly relies on positional information provided by perception of hormone gradients and non-cell autonomous factors (50-52). The expanded family of plant RLK proteins and their ligands play central roles in intercellular communication, cell identity maintenance, and the regulation of cell expansion and proliferation (53).…”
Section: Discussionmentioning
confidence: 99%
“…Protocols for single-cell lineage tracing were established in animal and human studies [ 96 ], and could be adapted for use in plant analysis. Recent single-cell analysis of Arabidopsis roots showed that multiple cell types could rapidly reconstitute stem cells by replaying the patterns of embryogenesis [ 33 ], therefore supporting the notion of a decentralised stem cell control system [ 97 ]. Single-cell transcriptomics can further contribute to the identification of critical genes in regeneration, which can be tracked and used as markers for developmental studies.…”
Section: Future Directions Of Single-cell Analysis In Plantsmentioning
confidence: 96%
“…For more extensive review, the reader is directed to [32]. For recent reviews of root apical meristem development and the maintenance of the root stem cell niche, see [33][34][35]. New COL cells are produced by COL stem cells (CSCs), which form one or two layers distal to the QC (Figure 1).…”
Section: Signaling Peptide and Transcriptional Regulation Of Blc Releasementioning
confidence: 99%